SEISMIC RESPONSE OF SINGLE SPAN MASONRY ARCH BRIDGES LOCATED IN ELAZIG AND MALATYA - Ozmen, Alper; Sayin, Erkut (Int Journal Bridge Engineering, 2023)
Historical masonry arch bridges are a major portion of the transportation network in the world. They are mostly constructed with brick and stone materials. These structures are reasonably important, for transferring the history and life style of ancient societies. They have to protect against the unexpected effects (i.e., floods, fire, and earthquake). Due to these factors, seismic behavior of these structures must be well known. In this paper, three different single span masonry arch bridges (Veli Palas, Musa Palas and Mavilik) were chosen as a case study. ANSYS software was used to generate three-dimensional finite element model of the bridges. 1992 Erzincan, 1999 Duzce and 2003 Bingol earthquake records were used for dynamic time history analyses. Displacements, principal stresses, potential damage regions and seismic response of masonry bridges were evaluated after the dynamic analyses.
Keywords: Dynamic Analyses; Masonry Bridge; Finite Element Model; Seismic Response